Professional development and innovative pedagogy in an online community through the lens of activity theory - Kaulback, Brenda G. (Proceedings of the International Conference on Networked Learning, 2012)
The liberation of learning from time and place constrictions through digital technologies has enabled the creation of new learning environments. This paper analyzes one such model, which was developed by those engaged in Global Skills for College Completion (GSCC), through the lens of activity theory. GSCC is an on-going national research project funded by the Bill and Melinda Gates Foundation in which twenty-five faculty from sixteen U.S. community colleges created an innovative developmental education[1] pedagogy in an online community. Through the use of a managed digital environment consisting of an electronic portfolio, an online collaborative space called Polilogue (a customized version of the open source web-based course management system, Moodle) and various other technologies, the faculty simultaneously developed and field-tested both a professional development model and a developmental education pedagogy for community college students. The premise of GSCC is that faculty participating collaboratively in the creation of an innovative pedagogy drawn from current practice of successful faculty and utilizing social media technologies can change teaching practice and improve student success. Pass rates from these community college classes nationally, which enroll more low-income, immigrant, and black and Latino students than four-year colleges, are barely 60 percent and the goal of GSCC is to push that to an 80% pass rate. This research project, which is both evidence-based and theory-driven, is in the final semester of the first phase. The project team includes faculty and administrators from LaGuardia Community College and consultants from Knowledge in the Public Interest. Several articles, chapters, papers and conference papers have been written and presented about GSCC (e.g. Woolis & Mellow, 2011; Woolis, Mellow, & Laurillard, 2011). A team of researchers from SRI International, an independent, nonprofit research institute, provides the research expertise for the project. The Center for Applied Research at Central Piedmont Community College collects and analyzes completion and pass rate data. This paper focuses on the professional development aspect of the project, the online pedagogy designed for the faculty themselves which incorporates dialogue, reflection, and practice. It considers three aspects of the project that are highlighted by an activity theory analysis: (1) the conjunction of the learning and knowledge creation systems, (2) the role of tags, themes and patterns in creating internal tensions and contradictions, and (3) the changed division of labor seen in the teaching/learning roles. [1] Basic skills and remedial education are other terms for developmental education.